Implementasi Kebijakan Disiplin Siswa Berbasis Qawāʿid Fiqhiyyah di MI Kotawaringin Barat - Baehaqi, Adham; Jasiah, Jasiah (Lembaga Teewan Journal Solutions, 2026)
Student discipline is an essential aspect of Islamic education aimed at fostering responsibility, orderliness, and moral character among learners. However, studies examining student discipline policies from the perspective of Qawāʿid Fiqhiyyah remain limited, particularly at the Islamic elementary school level. This study aims to analyze the implementation of student discipline policies based on Qawāʿid Fiqhiyyah in Islamic Elementary Schools (Madrasah Ibtidaiyah) in West Kotawaringin. A qualitative field research approach was employed, with data collected through observations, interviews, and documentation involving principals, teachers, and students. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that discipline policies are implemented through a structured classification of violations and educational sanctions emphasizing guidance rather than punishment. The practices reflect the principles of al-umūr bi maqāṣidihā, al-ḍarar yuzāl, al-masyaqqah tajlib al-taysīr, al-ʿādah muḥakkamah, and al-yaqīn lā yazūlu bi al-syakk. Teachers verify facts before imposing sanctions and provide flexibility for students with valid reasons. Nevertheless, several challenges remain, including inconsistent rule enforcement, limited parental involvement, insufficient teacher understanding of Qawāʿid Fiqhiyyah, and the absence of integrated written guidelines. The study concludes that the application of Qawāʿid Fiqhiyyah contributes positively to enhancing students’ responsibility and awareness of school regulations.